Efficacy of peroral endoscopic myotomy compared with other invasive treatment options for the different esophageal motor disorders - Fermín Estremera-Arévalo; Eduardo Albéniz; María Rullán; Irene Areste; Rosa Iglesias; Juan Vila (Revista Espanola de Enfermedades Digestivas)
Introduction: Peroral endoscopic myotomy (POEM) has been performed since 2008 on more than 5,000 patients. It has proven to be highly effective in the treatment of achalasia and has shown promising outcomes for other esophageal motility spastic disorders. Methods: A literature review of the efficacy of POEM compared to the previous invasive treatments for different esophageal motility disorders was performed. The application in the pediatric and elderly populations and its role as a rescue therapy after other procedures are also outlined. Results: Short-term outcomes are similar to laparoscopic Heller myotomy (LHM) and pneumatic endoscopic dilation (PD) (clinical success > 90%) for achalasia subtypes I and II. Mid-term outcomes are comparable to LHM and overcome results obtained after PD (> 90% vs ~50%). With regard to type III achalasia, POEM efficacy is 98% compared to 80.8% for LHM and the PD success remains at 40%. With regard to spastic esophageal disorders (SED), POEM has an effectiveness of 88% and 70% for distal esophageal spasm (DES) and jackhammer esophagus (JE) respectively. A response of 95% in patients with sigmoid esophagus has been reported. POEM has been performed in pediatric and elderly populations and has obtained a higher efficacy than PD in pediatric series (100% vs 33%) without greater adverse events. Previous treatments do not seem to hinder POEM results with excellent response rates, including 97% in post LHM and 100% in a re-POEM series. Final considerations: POEM has shown excellent short and mid-term results for all subtypes of achalasia but long-term results are not yet available. The promising results in SED may make POEM the first-line treatment for SED. A high-safety profile and efficacy have been shown in elderly and pediatric populations. Previous treatments do not seem to diminish the success rate of POEM. Core tip: POEM has emerged as an efficient treatment option for all subtypes of achalasia and other scenarios (including previous treatments and elderly and pediatric populations). Short and mid-term results are comparable to LHM and are better than PD data. The clinical response rate of DES and JE may make POEM the first-line treatment for SED.